Meningkatkan Kedisiplinan Siswa Melalui Implementasi Manajemen Bimbingan dan Konseling - Ida lutfiyatul Jamilah; Nur Indah Rofiqoh (Pascasarjana Universitas Qomaruddin, 2023)
It needs to be emphasized that students are experiencing a phase of development and growth in accordance with their nature. Therefore, they need consistent guidance and direction to achieve their natural potential optimally. The task of guiding and directing is the responsibility of teachers in an educational institution, especially in managing students in their institution. Student management is an integral part of the world of education. The research method used is qualitative with a descriptive approach, especially field survey research. The analysis was carried out descriptively to provide a quick and precise picture of the implementation of guidance and counseling management in improving student discipline at Sunan Drajat Lamongan Vocational School. The results of the research show that the implementation of guidance and counseling management at Sunan Drajat Lamongan Vocational School to improve student discipline is quite good, involving preventive and control measures. BK teachers actively guide, direct and provide solutions to student problems to prevent violations of school rules.